Relational resources as a source of regional competitive advantage: Illustrated by the examples of the Lodzkie Voivodship and the novosibirsk oblast - Wawrzyniec Rudolf; Alʹmira T. Jusupova (Comparative Economic Research. Central and Eastern Europe, 2015)
The paper aims to show relational resources as an increasingly significant factor in the competitiveness of territories. The authors argue that regions trying to increase their competitive position should undertake actions to facilitate the creation of a knowledge base and an institutional environment. This elaboration relies on the resource-based theory, used especially for analyzing relations between an organization and its environment. The paper presents theoretical considerations based on the desk research methodology and worldwide literature. Descriptive characterizations of two cases complete the presentations. The paper presents examples of two regions from different socio - economic systems, illustrating the role of relational resources in their development policy. These regions are the Lodz Voivodeship in Poland and the Novosibirsk Oblast of the Russian Federation. In their home countries, both of them had a strong economic position before the 1980's, and in the time of today's recession are considered as regions with a slightly above-average potential for growth and good prospects for the development of their economy. Their current competitive positions in the investment market, in comparison with other regions in their countries, are also presented. The paper presents evidence that activities aimed at supporting relational resources (innovation policy, cluster development, cooperation between authorities and regional stakeholders) are conducted on a large scale. It also shows the importance given to relational resources in the developmental strategies of both regions. However, determinants resulting from the socioeconomic system and regional qualifications in the area of development management provide different opportunities to use these resources in practice.
Keywords: 330; regional competitiveness; relational resources; economic institutions; regional stakeholders